Innovative research of ornamental plants in University of Debrecen (2001–2014) - Kaprinyák, T. (International Journal of Horticultural Science, 2014)
In the University of Debrecen started in 2001 related and biotechnology, genetic researches on climate-changerelated. This work has already visible signs on the city’s public spaces. The main goal of participants of the program is it that in Debrecen and in the surrounding communities more adaptable to the variable climate, ecologically and biologically more grounded urban ornamental planting are preferred in the next decade. The new results and ongoing researches of the decorative ornamental and biomass plants are an interdisciplinary breeding program.